Allene oxide synthase, allene oxide cyclase and jasmonic acid levels in Lotus japonicus nodules - Zdyb, Anna; Salgado, Marco G.; Demchenko, Kirill N.; Brenner, Wolfram G.; Płaszczyca, Małgorzata; Stumpe, Michael; Herrfurth, Cornelia; Feussner, Ivo; Pawlowski, Katharina (PLOS ONE, 2018)
Jasmonic acid (JA), its derivatives and its precursor cis-12-oxo phytodienoic acid (OPDA) form a group of phytohormones, the jasmonates, representing signal molecules involved in plant stress responses, in the defense against pathogens as well as in development. Elevated levels of JA have been shown to play a role in arbuscular mycorrhiza and in the induction of nitrogen-fixing root nodules. In this study, the gene families of two committed enzymes of the JA biosynthetic pathway, allene oxide synthase (AOS) and allene oxide cyclase (AOC), were characterized in the determinate nodule-forming model legume Lotus japonicus JA levels were to be analysed in the course of nodulation. Since in all L. japonicus organs examined, JA levels increased upon mechanical disturbance and wounding, an aeroponic culture system was established to allow for a quick harvest, followed by the analysis of JA levels in whole root and shoot systems. Nodulated plants were compared with non-nodulated plants grown on nitrate or ammonium as N source, respectively, over a five week-period. JA levels turned out to be more or less stable independently of the growth conditions. However, L. japonicus nodules formed on aeroponically grown plants often showed patches of cells with reduced bacteroid density, presumably a stress symptom. Immunolocalization using a heterologous antibody showed that the vascular systems of these nodules also seemed to contain less AOC protein than those of nodules of plants grown in perlite/vermiculite. Hence, aeroponically grown L. japonicus plants are likely to be habituated to stress which could have affected JA levels.